2014
DOI: 10.1016/j.humimm.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor: Association of −794 CATT5–8 and −173 G>C polymorphisms with TNF-α in systemic lupus erythematosus

Abstract: Macrophage migration inhibitory factor (MIF) is an upstream immunoregulatory cytokine associated with the pathogenesis of autoimmune inflammatory diseases. There is evidence that MIF functions in a positive feedback loop with TNF-α that could perpetuate the inflammatory process in systemic lupus erythematosus (SLE). In this case-control study we investigated whether commonly occurring functional MIF polymorphisms are associated with SLE as well as with MIF and TNF-α serum levels in a Mexican-Mestizo population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
5
37
1
Order By: Relevance
“…Our genetic data indicate that patients with GPA had a greater prevalence of high MIF expression (i.e., >À794 CATT 5 ) genotypes when compared to healthy controls. These findings mirror the associations that have been reported previously between MIF polymorphisms and disease susceptibility or clinical severity in several autoimmune diseases, including systemic lupus erythematosus (13,42), scleroderma (14), rheumatoid arthritis (15,43), autoimmune liver disease (44), and celiac disease (45), as well as in granulomatous conditions such as sarcoidosis (6) and tuberculosis (25,46). Furthermore, higher MIF plasma levels were noted in patients with GPA compared to healthy controls, a finding previously reported in AAV and other granulomatous diseases (8,47,48).…”
Section: Discussionsupporting
confidence: 90%
“…Our genetic data indicate that patients with GPA had a greater prevalence of high MIF expression (i.e., >À794 CATT 5 ) genotypes when compared to healthy controls. These findings mirror the associations that have been reported previously between MIF polymorphisms and disease susceptibility or clinical severity in several autoimmune diseases, including systemic lupus erythematosus (13,42), scleroderma (14), rheumatoid arthritis (15,43), autoimmune liver disease (44), and celiac disease (45), as well as in granulomatous conditions such as sarcoidosis (6) and tuberculosis (25,46). Furthermore, higher MIF plasma levels were noted in patients with GPA compared to healthy controls, a finding previously reported in AAV and other granulomatous diseases (8,47,48).…”
Section: Discussionsupporting
confidence: 90%
“…The articles were subjected to screening, and 31 duplicate articles as well as 202 articles with reviewed titles and abstract were excluded. Twenty-two articles were retrieved for further detailed assessments, and 9 articles were further excluded (3 have no full texts, 3 have no available data, and 3 were only review papers), leaving 13 articles meeting the inclusion criteria [16][17][18][19][20][28][29][30][31][32][33] (Figure 1). Among the 13 included articles, 5, 3, 1, and 1 were from PubMed [16,18,20,28,29,32], Embase [17,30,31], Web of Science [19], and several Chinese databases [33], respectively.…”
Section: Literature Searchmentioning
confidence: 99%
“…Over the years, some studies have indicated plasma/serum MIF level in patients with SLE and demonstrated that plasma/serum MIF level differs in SLE patients. In addition, several studies have explored the association of MIF-173 C/G and -794 CATT polymorphisms with susceptibility to SLE, but with a smaller sample size compared to the overall sample size of this study [16][17][18][19][20]. However, the difference in the various studies cannot be elucidated by standard units, ethnicity, and characteristic differences in healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that MIF levels are increased in patients with rheumatoid arthritis [17], systemic lupus erythematosus [18], insulin resistance [19], and type 2 diabetes mellitus [20]. As all these disorders are associated with persistent inflammation, it is important to elucidate the role of MIF in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%